Digitalisation and customer acquisition in companies in Latin America. A systematic review of the literature 2013-2023. (LACCEI, 2024)
The present study has the objective to analyze digitization and how it can help companies to attract their customers to retain them through the different strategies that are applied in the most efficient way possible, based on digital innovations. Customer acquisition is a very sensitive activity, because of customer satisfaction for their experiences and service rating, which allows to value and obtain constant feedback to design strategies, automate communication processes, campaigns. It is at this point that digitization, like that technological innovation, contributes to a better relationship with our customers, generates trust and the company has a competitive advantage. It is generated in a documentary way, fundamentals and relevant aspects focused on promoting the growth of companies through this digitization, to expand their market and encourage confidence in the services generated, this allows companies to adapt to the facilities that require the customer and automate customer service processes, advertising, campaigns. It concludes by sharing a practical guide with customer acquisition and loyalty strategies based on digitization.